1998
DOI: 10.2166/wst.1998.0705
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of biofouling by extracellular polymers in a membrane separation activated sludge system

Abstract: A Laboratory-scale experiment was conducted to investigate the mechanism of the bio-fouling in the submerged membrane separation activated sludge system. Flat-sheet-type membrane module was used and the change of the pressure and the filtration resistance was measured. Two reactors were operated in parallel to investigate the influence of organic loading rate on the reactor performance. A mathematical model was developed to simulate temporal changes of suction pressure, flux and filtration resistance consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 0 publications
4
51
0
1
Order By: Relevance
“…Nagaoka et al [28] investigated the influence of OLR on membrane fouling in two parallel submerged MBR s, and found that the high OLR (1.5 g-TOC/L/day) showed a sudden increase of the pressure and a decrease of flux after 40th days, which could not be recovered even by membrane cleanings, while the low OLR (0.5 g-TOC/L/ day) showed little increase of the pressure until 120th days. The data obtained from the current investigation, together with previous work in the literature, indicate that HRT or OLR was a very significant operating parameter that affects membrane performance in MBR systems.…”
Section: Performance Of the Mbrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nagaoka et al [28] investigated the influence of OLR on membrane fouling in two parallel submerged MBR s, and found that the high OLR (1.5 g-TOC/L/day) showed a sudden increase of the pressure and a decrease of flux after 40th days, which could not be recovered even by membrane cleanings, while the low OLR (0.5 g-TOC/L/ day) showed little increase of the pressure until 120th days. The data obtained from the current investigation, together with previous work in the literature, indicate that HRT or OLR was a very significant operating parameter that affects membrane performance in MBR systems.…”
Section: Performance Of the Mbrsmentioning
confidence: 99%
“…The composition and quantity of the organic fraction of the EPS would correlate to the membrane fouling [41]. Nagaoka reported that the high OLR could lead to much production of EPS and result in severe membrane fouling [28].…”
Section: Evolution Of Eps In Sludge Suspensionmentioning
confidence: 99%
“…Their model assumed that a fraction of SMPs was retained in the reactor due to membrane rejection, since part of the SMP was comprised of macromolecules. A model to predict membrane fouling taking into account the accumulation of ECP in a submerged membrane activated sludge process was also proposed by Nagaoka et al 18 According to these authors the measured pattern of changes in flux, pressure and resistance was explained well by the model, which assumed that ECP accumulates on the membrane by advection, while it is detached from the biomass by shear stress.…”
Section: Introductionmentioning
confidence: 99%
“…However, a significant increase in MLSS concentration was observed while decreasing the HRT from 15 h to 12, 9 and 6 h because shorter HRT provides more nutrients to the biomass and leads to a higher biological growth and so a higher MLSS (Dufresne et al 1998). According to Nagaoka et al (1998), MLSS is also directly influenced by organic loading rate (OLR); therefore, when OLR was varied from 1 to 2 and 3 g/L day on each HRT, an increase in MLSS concentration was also reported, as shown in Fig. 2.…”
Section: Effect Of Hrt On Biomass Concentration and Tmpmentioning
confidence: 99%